2011
DOI: 10.1242/dev.069203
|View full text |Cite
|
Sign up to set email alerts
|

ID4 regulates mammary gland development by suppressing p38MAPK activity

Abstract: SUMMARYThe ID family of helix-loop-helix proteins regulates cell proliferation and differentiation in many different developmental pathways, but the functions of ID4 in mammary development are unknown. We report that mouse Id4 is expressed in cap cells, basal cells and in a subset of luminal epithelial cells, and that its targeted deletion impairs ductal expansion and branching morphogenesis as well as cell proliferation induced by estrogen and/or progesterone. We discover that p38MAPK is activated in Id4-null… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 41 publications
4
43
0
Order By: Relevance
“…The identity of these transcriptional regulators is currently unknown. Loss-of-function studies have confirmed the requirement for ID4 in ductal morphogenesis in the developing pubertal mammary gland (Dong et al 2011, Best et al 2014, Junankar et al 2015, with ID4-positive cells repopulating the adult mammary gland at a greater frequency than ID4-negative cells demonstrating the intrinsic stem cell activity of the ID4-positive basal cells (Junankar et al 2015). ID4-knockout mice also have delayed ductal morphogenesis further signifying the requirement for this transcription factor in mammary gland development (Dong et al 2011, Junankar et al 2015.…”
Section: Id4 In the Mammary Glandmentioning
confidence: 94%
See 1 more Smart Citation
“…The identity of these transcriptional regulators is currently unknown. Loss-of-function studies have confirmed the requirement for ID4 in ductal morphogenesis in the developing pubertal mammary gland (Dong et al 2011, Best et al 2014, Junankar et al 2015, with ID4-positive cells repopulating the adult mammary gland at a greater frequency than ID4-negative cells demonstrating the intrinsic stem cell activity of the ID4-positive basal cells (Junankar et al 2015). ID4-knockout mice also have delayed ductal morphogenesis further signifying the requirement for this transcription factor in mammary gland development (Dong et al 2011, Junankar et al 2015.…”
Section: Id4 In the Mammary Glandmentioning
confidence: 94%
“…Similarly, ID4 is expressed in hormonally regulated tissues including the breast, ovaries and prostate and is required for normal development (Shan et al 2003, Dong et al 2011, Sharma et al 2013, Best et al 2014, Junankar et al 2015. ID4 is stimulated by progesterone receptor (PR) activity through direct binding of ligand-activated PR to the ID4 promoter (Fernandez-Valdivia et al 2008).…”
Section: :9mentioning
confidence: 99%
“…Only 20% of mice survive on an Id4-null background, following a high proportion of embryonic and post-partum lethality resulting from severe brain and neuronal abnormalities (Bedford et al, 2005;Yun et al, 2004). In the male reproductive system, Id4 loss results in significantly reduced seminal vesicle size, prostatic intraepithelial neoplasia (PIN) lesions and sterility (Sharma et al, 2013), while a recent study in the mammary gland has shown that Id4 governs ductal elongation and branching via the Id4 target p38MAPK (Dong et al, 2011). In breast epithelial cells, Id4 negatively controls expression of the key tumor suppressor Brca1 (Beger et al, 2001) and also suppresses miR335, a positive regulator of Brca1 (Heyn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In Wnt4 -/− and Id4 −/− (REF. 82) mammary epithelia side branching is delayed. The role of calcitonin awaits further studies.…”
Section: Progesterone-induced Changesmentioning
confidence: 99%
“…Ectopic expression of its cousin WNT1 can rescue side branching by a paracrine mechanism in the absence of PR signalling 56 . Similarly, inhibitor of DNA binding 4 (ID4), a basic helix-loop-helix (bHLH) protein that is predominantly expressed in the myo epithelium is induced by progesterone, and its deletion in the mammary epithelium blocks side branching 82 . Calcitonin and amphiregulin have also been identified as in vivo progesterone targets 83 .…”
Section: Progesterone-induced Changesmentioning
confidence: 99%